Effect of Ring Material and Diameter on Orthopedic Implant Stability: External Fixation in Femur Bone - Fatin Izzati Ibrahim, Nur; Daud, Ruslizam; Khairul Ali Hassan, Muhammad; Ali Hassan, Noor; Alia Md Zain, Noor; Saifullah Kamaruddin, Nur; Fahmi Azizan, Asrul; Bajuri, Yazid (International Journal of Engineering and Technology, 2018)
Axial stiffness is the most important factor in stability. It is known that any changes in the diameter of any components of the frame will either increase or decrease the axial stiffness of the fixation. The model of implant and bone will be variety as the variables changes. Current studies states that ring stability are one of the most important factors in ensuring fractured bones to have a successful re-union. In circular external fixation, the stability of the pin-bone interaction is influenced by the stability of the fixation frame where the major component is the rings. The objective is to study the finite element analysis (FEA) of the external fixator assembled in human diaphysis under compression force with different materials of the exoskeleton which are stainless steel, titanium alloy, magnesium alloy and carbon fiber. The results obtained show the mechanical strength of each material where it will be used to compare the value of von-Mises stress, stiffness and total deformation to acquire the best suitable ring diameter and material. Based on the result, as the diameter of the ring increases, the stiffness of the ring will be decreased.Â